A new species of Phymastichus (Hymenoptera: Eulophidae: Tetrastichinae) parasitic on Xyleborus beetles (Coleoptera: Curculionidae: Scolytinae) in Hawaiʻi, and aspects of its biology, life history, and behavior - Honsberger, David N; Wright, Mark G (Zootaxa, 2022)
A third species in the genus Phymastichus LaSalle (Hymenoptera: Eulophidae), Phymastichus holoholo sp. nov., is described from specimens endoparasitic on adult Xyleborus beetles in Hawaiʻi. Plant and insect host records known for this species, and aspects of its searching, oviposition, and emergence behavior are discussed and illustrated with photographs and video. This new species, along with Phymastichus xylebori which is also present in Hawaiʻi, has potential as a biological control agent against Xyleborus beetles where they are problematic. Of special interest is their potential as natural enemies of X. ferrugineus, X. affinis, and X. perforans, which have recently been implicated in possibly spreading Rapid ʻŌhiʻa Death in Hawaiʻi. Some aspects of their potential use to combat this disease, as well as some important but as of yet unanswered questions, are discussed. Two observed instances of parasitism by the newly described species of beetles in the Euwallacea fornicatus species complex, Euwallacea fornicatus (sensu stricto) and Euwallacea perbrevis, are also reported.